2020
DOI: 10.1017/s0007114520000756
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mycoprotein on glycaemic control and energy intake in humans: a systematic review

Abstract: Mycoprotein is a food high in both dietary fibre and non-animal-derived protein. Global mycoprotein consumption is increasing, although its effect on human health has not yet been systematically reviewed. This study aims to systematically review the effects of mycoprotein on glycaemic control and energy intake in humans. A literature search of randomised controlled trials was performed in PubMed, Embase, Web of Science, Google Scholar and hand search. A total of twenty-one studies were identified of which only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 48 publications
3
28
1
Order By: Relevance
“…Acute and chronic intervention studies suggest that mycoprotein may have a positive effect on glycaemia, insulinaemia, lipidemia, appetite regulation and energy intake [13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute and chronic intervention studies suggest that mycoprotein may have a positive effect on glycaemia, insulinaemia, lipidemia, appetite regulation and energy intake [13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…Mycoprotein-based foods are commercially available under the brand name of Quorn in 17 countries across the world, and is growing in popularity in the UK as meat replacements 12 . A recent systematic review suggested that an acute intake of mycoprotein increases insulin sensitivity and decreases energy intake in healthy lean and overweight individuals compared to matched animal-derived protein 13 . In addition, chronic mycoprotein interventions have resulted in a reduction in low-density lipoprotein cholesterol (LDL-C) and total cholesterol (TC) in both controlled and free-living settings [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Mycoprotein is high in protein, provides the full range of essential amino acids, is low in fat, low in saturated fat, high in fibre and a source of riboflavin, folate, magnesium, phosphorous, copper, zinc, selenium and choline [ 96 ]. Alongside the recent systematic review showing that mycoprotein ingestion is associated with reduced insulin levels [ 27 ] at least 13 separate human studies have studied inter-relationships between mycoprotein consumption and human health [ 8 ], and more in recent years. Fungi are known to be rich sources of ergothioneine and glutathione, which are both potent antioxidants with potential anti-inflammatory properties [ 97 ].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Other work has observed notable improvements in markers of glycaemia and insulinaemia, including reduced insulin levels and sustained hyperinsulinaemia and hyperaminoacidaemia [ 74 , 77 , 88 , 89 ]. As shown in Table 1 , results collated from five trials found that mycoprotein ingestion was associated with reduced insulin levels and appeared effective at reducing ad libitum energy intake in health lean, overweight and obese adults [ 27 ].…”
Section: Mycelium/fungal-derived Proteinsmentioning
confidence: 99%
“…(i) He et al (4) (ii) Cherta-Murillo et al (5) Cox encourages authors to be creative in designing their graphical abstracts and has suggested that this may lead to more interest in their research. In turn, this may result in unexpected collaborations, more citations, and more research funding and recognition (3) .…”
mentioning
confidence: 99%